CORRELATION BETWEEN STUDENTS’ PEFORMANCE IN MICRO TEACHING AND FIELD PRACTICE TEACHING OF THE SEVENTH SEMESTER ENGLISH STUDENTS AT FKIP UIR - Idayani, Andi (UIR Press, 2017)
ABSTRACTMicro teaching is a teacher training technique for learning teaching skill. It employsreal teaching situation for developing skills and helps to get deeper knowledgeregarding the art of teaching. However, the teachers may give necessary backgroundfor the observation of a model or demonstration lesson on the selected teaching skill.Hence, Interest of becoming teacher is a person desire for something related to hisfuture or aims. It becomes an interest for a profession. Indeed, emerging the interest,one should be aware of his potency and capabilities he possesses. This study focuseson students’ peformance in micro teaching and field practice teaching at the seventhsemester of English Students of FKIP UIR which consists of 23 students as sample ofthis research. The researchers used descriptive method and have used score frommicro teaching and field practice teaching and questionnaires as a collecting data ofresearch. After collecting data from questionnaires and calculated the correlationbetween micro teaching score and field practice teaching score, the researchers havefound that robs was higher than r table( 0,713> 0,413) at level significant 5% and it wasthe same at level significant 1% the robs was higher than r table (0,713 > 0,525), fromthe result it can be concluded that null hypothesis (Ho) was rejected and alternativehypothesis (Ha) was accepted. Then, the coefficient correlation of robserved was 0,713, itmeans that there was a high correlation between students’ peformance in microteaching and their performance in field practice teaching.